Laboratorij za metrologijo tlaka na Inštitutu za kovinske materiale in tehnologije - Šetina, Janez (Materiali in tehnologije, 2001)
The Laboratory of Pressure Metrology (LMT) at the Institute of Metals and Technology (IMT) plans to become the top-level laboratory in the Slovenian national metrology system for the derived quantity of pressure. The laboratory will provide the international traceability to the highest-level reference pressure standards and dissemination to lower hierarchical levels within the country. The laboratory performs calibrations of pressure gauges by direct comparison with reference gauges. The range of the laboratory's capabilities extends from vacuum at 10$^-5$ Pa up to high pressures of 200 MPa. The laboratory has applied for accreditation at Slovenian Accreditation and expects to earn it towards the end of this year. The scope of accrteditation will be the calibration of pressure gauges in the range from 100 Pa to 7 MPa. The laboratory is also active in the field of scientific metrology of the measurable quantity pressure. Research and development work is mainly focused on the development of horizontal traceability of a low-range piston gauge to Slovenian national standards of base quantities of the SI system, the extension of the pressure scale to lower pressures by static expansion in gases and studies of metrological characteristics of vacuum-transfer standards.
Keywords: merjenje tlaka; vakuum; sledljivost; kalibracija; etaloni